Development of an ESD-oriented Energy Teaching Module with A Differentiated Learning Approach - Wahyuni, Sri; Khoiri, Nur; Novita, Mega (KnE Social Sciences, 2024)
In the modern era of dependence on energy resources, insufficient understanding of energy concepts can hinder an individual’s ability to make wise decisions about energy use, address environmental problems, and contribute to sustainable development. The urgency of integrating education for sustainable development (ESD) into an educational curriculum that is adapted based on students’ conditions is becoming increasingly clear. This research aims to develop a teaching module on energy concepts oriented toward ESD with a differentiated learning approach (teaching at the right level). The module development methodology follows the analysis, design, development, implementation, and evaluation (ADDIE) framework, focusing on the development stage. The development process involved in-depth analysis of the different ESD learning needs of students, so that the modules could be tailored to their level of understanding and learning styles. The results of this research are teaching modules that are innovative and relevant to global energy and ESD issues. This module has not yet undergone the implementation stage but has gone through a careful development stage. The benefits of teaching modules developed with a differentiated approach to energy concepts, within the ESD framework, can contribute to a better understanding of energy and sustainability issues throughout the world. Keywords: differentiated learning, ESD, energy, teaching module